Differences in mandibular morphology between bruxism and non-bruxism patients based on the Levandoski analysis - Aufa, Aghitsna Aulia; Rikmasari, Rasmi; Wulansari, Daisy (Faculty of Dentistry, Universitas Gadjah Mada, 2022)
Bruxism is a condition that involves grinding and clenching which can place a large load on the mandible, so it can change the morphology of the mandible. Based on the Levandoski analysis, this study aimed to determine whether there are differences in the mandibular morphology between bruxism and non-bruxism patients. This study was a cross-sectional analytic study conducted on the panoramic radiographic samples of bruxism and non-bruxism patients with a total sample of 30 patients (n = 30) in each group, obtained from the radiographic archives at the Radiology Installation of RSGM Universitas Padjadjaran which have been confirmed as bruxism and non-bruxism patients. Measurements were carried out using ImageJ software based on the reference lines by Levandoski. The results of the study were analyzed using SPSS software by performing normality and homogeneity tests, followed by a statistically independent t-test or Mann-Whitney test. The results of the independent t-test showed that three lines had a p-value < 0.05, namely the line from the point gonion to the maxillary vertical line on the right side, the distance from the top point of the condyle to the maxillary interincisal point on the right side, and the distance from the top point of the condyle to the mandibular interincisal point on the right side. The Mann-Whitney test results showed that two lines had a p-value < 0.05, namely the maxillary vertical midline and the distance from the condyle to the left maxillary vertical line. The other line had a p-value> 0.05. There were differences in the mandibular morphology between bruxism and non-bruxism patients based on the Levandoski analysis, namely the length of the maxillary vertical midline, the distance from the condyle top point to the maxillary vertical midline, the distance from the point gonion to the maxillary vertical midline, the distance from the top point of the condyle to the maxillary interincisal point on the left side, and the distance from the top point of the condyle to the mandibular interincisal point on the left side. On the other four lines, there was no significant difference between bruxism and non-bruxism patients.